Efeito da dieta à base de soja e do estado nutricional pregresso sobre a via inflamatória no fígado, tecido adiposo e hipotálamo e a homeostase glicêmica em ratos - Laux, Michele Cristiane (2018)
We evaluated involvement of inflammation in the liver, rWAT and hypothalamus on the insulin signaling pathway and glycemic homeostasis in rats recovered from protein restriction in intrauterine life and lactation with soybean diet for 37 or 60 days. Male rats from mothers fed either 17 or 6 % protein during pregnancy and lactation were maintained on 17 % casein (CC and LC groups), 17 % soybean (CS and LS groups) diets over 35 or 60 d. After 35 d of soybean diet intake TNFα expression was increased, pJNK content was unaltered, but p-Akt level was reduced in hepatic tissue. Small adipocytes were more frequent than large adipocytes, especially in LS rats. LS and CS groups showed high p-Akt despite elevation of TNFα. In hypothalamus, soybean diet reduced p-Akt content but with unaltered TNFα. After 60 days of soybean diet intake, LS rats had lower TNFα, pJNK and p-Akt in liver compare to CC or CS. Adipocytes from LS and CS had high TNFα, p-Akt levels and increased adipocytes area. Hypothalamus from LS and CS groups showed increase of TNFα content, but diminished p-Akt level. Thus, inflammation produced by soybean diet contributed to insulin resistance in the liver and hypothalamus, being that on the last tissue this association was time-dependent. The reduced glycemia observed in LS and CS rats can to have resulted from increased insulin sensitivity in the adipose tissue. The effect of soybean diet on inflammatory process differed in function of previous nutritional status.